2017
DOI: 10.9734/ajob/2017/33500
|View full text |Cite
|
Sign up to set email alerts
|

Bio-insecticidal and Grain Protectant Activities of Mixed Powder of Ocimum gratissimum and Vernonia amydalina against Callosobruchus maculatus (Coleoptera: Bruchidae) in Calabar, Nigeria

Abstract: The bio-insecticidal and grain protectant activities of mixed powder of Ocimum gratissimum and Vernonia amygdalina upon Callosobruchus maculatus was carried out in Calabar, Nigeria during the dry season (August to November) of 2015. The mortality rate of cowpea weevil treated V. amygdalina: O. gratissimum at 100: 0 concentrations were 17.0%, 27.0%, and 47.0% for a period of 24hrs, 48hrs and 72hrs, respectively. Concentrations 0:100 gave a percentage mortality of 47.0%, 67.0% and 73.0% at 24hrs, 48hrs and 72hrs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…This suggests that, the V. heterophylla powder's effects being low at the 0.5 g dose become important after combination with the powders of another plant family. From these results, it can be suggested that the combination of the powders would increase the insecticidal compounds and the consequence would be the occurrence of high mortalities due to the additive effects of these compounds in a limited time [41]. Singh and Allen [42] showed that not only the combination of powders increases the majority compounds, but that the minority compounds in contact with the more active others, were able to significantly increase their activity.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that, the V. heterophylla powder's effects being low at the 0.5 g dose become important after combination with the powders of another plant family. From these results, it can be suggested that the combination of the powders would increase the insecticidal compounds and the consequence would be the occurrence of high mortalities due to the additive effects of these compounds in a limited time [41]. Singh and Allen [42] showed that not only the combination of powders increases the majority compounds, but that the minority compounds in contact with the more active others, were able to significantly increase their activity.…”
Section: Discussionmentioning
confidence: 99%